The March 5, 1987, Ecuador earthquakes : mass wasting and socioeconomic effects - Schuster, Robert L.; Egred, José (Natural disaster studies, 1991)
This book provides an account of the 1987 Ecuador earthquakes, evaluating the physical phenomena involved and the performance of structures and systems. It identifies and recommends cases where an in-depth study would contribute to improvement of our ability to analyze and forecast such failures and our preparedness, warning, rescue, recovery, and rehabilitation systems. The volume also describes how state-of-the-art knowledge can be applied to improve public safety and welfare.